Solar Water Splitting: Enhancing Charge Carrier Lifetime in Metal Oxide Photoelectrodes through Mild Hydrogen Treatment (Adv. Energy Mater. 22/2017). Issue 22 (22nd November 2017) - Jang, Ji‐Wook; Friedrich, Dennis; Müller, Sönke; Lamers, Marlene; Hempel, Hannes; Lardhi, Sheikha; Cao, Zhen; Harb, Moussab; Cavallo, Luigi; Heller, René; Eichberger, Rainer; van de Krol, Roel; et al.
Abstract : Time‐resolved conductivity measurements reveal that a mild hydrogen treatment at 300 °C for 10 minutes successfully extends the lifetime of carriers by more than two‐fold in bismuth vanadate (BiVO4 ) photoelectrodes. This enhancement is a result of passivation of deep trap states and/or reduction of their density. Consequently, the AM1.5 photocurrent and onset potential for the hydrogen‐treated BiVO4 are significantly improved. This is reported by Fatwa F. Abdi and co‐workers in article number1701536 .